P27. Altered regional and interregional interrelations of glutamate and GABA in patients with chronic low back pain – A 1H-MR spectroscopic study. Issue 8 (August 2015) - Gussew, A.; Borys, C.; Janetzki, L.; Cleve, M.; Malessa, R.; Habenicht, U.; Strauß, B.; Reichenbach, J.
<x xml:space="preserve">Abstract</x> Purpose Chronic pain is in many cases associated with a poor quality of life and high health care costs. Due to the multimodal disease origin, therapeutic methods are often rather unspecific. By applying modern functional imaging methods, neuronal dysfunction has been recently identified in patients and has been hypothesized to reflect the disease related central sensitization of neuronal pain processing (Farmer, 2012). However, the underlying neurochemical processes, especially changes in neurotransmitter turnover, remain widely unexplored although their understanding might be essential to improve current therapeutic approaches (Borsook, 2007). <alternatives><inline-graphic xlink:href="ark:/27927/pgj1f28fr45" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />1</alternatives>H-MR spectroscopy allows in vivo quantitation of glutamate and GABA, which are two of the most important neurotransmitters, and provides direct insight into chronic pain related neurochemical changes (Harris, 2012). In the present study, GABA and glutamate were quantified in three different pain processing regions of the brain of patients with unspecific chronic low back pain and compared to healthy subjects in order to investigate potentially altered regional and interregional neurochemical interrelations. Methods 13 patients (12f/1m) and 13 age and gender matched healthy subjects (54 ± 8 years) participated in this study. Patients underwent detailed clinical evaluation to assess their chronic pain state and adjacent effects. All measurements were performed with a whole-body 3T MR scanner (Siemens, Germany). Conventional and spectrally edited <alternatives><inline-graphic xlink:href="ark:/27927/pgj1f28fx6v" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />1</alternatives>H-MR spectra were collected from the anterior cingulate cortex (aCC), left insula (Ins) and posterior cortex (PC) with a PRESS sequence (TR/TE: 1800/30 ms) and a MEGAPRESS sequence (TR/TE: 1800/68 ms), respectively (Fig. 1). Sum intensities of glutamate and glutamine (Glx) were quantified from conventional spectra by using the LCModel (Provencher, 1993), whereas the GABA intensities were determined from the edited spectra with the jMRUI package (Stefan, 2009). Afterwards, all intensities were normalized with the corresponding creatine intensity. Regional and interregional interrelations were determined by means of Pearson correlations between GABA and Glx within as well as between the examined brain regions and compared between the two groups. Results and discussion Fig. 1 shows the correlation matrix with significant (p < 0.05) regional and interregional correlations between the neurotransmitters in healthy controls as well as selected data distributions obtained in healthy controls (in black) and patients (in red). Healthy subjects had a negative correlation between Glx and GABA in aCC. Glx in the Ins and PC was positively associated with Glx in aCC but negatively with GABA. These findings may indicate a neurotransmitter mediated regulation of functional interrelations between pain processing brain regions in the healthy state. Interestingly, patients did not show any comparable metabolic associations, which might be ascribed to disordered functional pathways due to the disease.